Elevating reactivity and cyclability of all-solid-state lithium-sulfur batteries by the combination of tellurium-doping and surface coating. (October 2020) - Zhang, Wei; Zhang, Yunyang; Peng, Linfeng; Li, Shuping; Wang, Xumin; Cheng, Shijie; Xie, Jia
Abstract: Considering its high theoretical energy density and high safety, the all-solid-state lithium-sulfur battery (ASSLSB) has become a promising candidate for the next-generation energy storage system. However, the low reactivity of sulfur and high interfacial resistances between the cathodes and solid electrolytes seriously hinder the practical application of high performance ASSLSBs. Sulfurized polyacrylonitrile (S@pPAN), which can effectively alleviate the volume expansion of sulfur, is a suitable choice for the sulfur cathode, but shows limited performance in ASSLSB. Here, we demonstrate a tellurium-doped S@pPAN (Te0.05 S0.95 @pPAN) cathode coated with solid electrolyte (Li7 P3 S11 ) for an ASSLSB with high reactivity and significant cycling stability. Benefiting from the thin layer coating of Li7 P3 S11 and the effect of Te-doping, the Te0.05 S0.95 @pPAN@Li7 P3 S11 composite delivers significantly enhanced reaction kinetics and excellent interfacial compatibility with the solid electrolyte. At room temperature, the assembled ASSLSB exhibits excellent rate and long cycling performance, with a reversible capacity over 1173.1 mAh g −1 and stable cycling over 500 cycles. The strategy of Te-doping and surface coating not only is facile and promising, but also provides guidance for constructing applicable ASSLSBs. Graphical abstract: A facile strategy involving Te-doping and surface coating is demonstrated in modifying sulfurized polyacrylonitrile (S@pPAN) cathode for all-solid-state lithium-sulfur battery (ASSLSB). Benefiting from the thin layer coating of Li7 P3 S11 and the effect of Te-doping, the Te0.05 S0.95 @pPAN@Li7 P3 S11 composite exhibits elevated reactivity and cycling stability, resulting in a high performance ASSLSB. Image 1 Highlights: ● A facile strategy using Te-doping and surface coating is shown to modify the cathode for a high performance all-solid-state lithium-sulfur battery. ● Through an in situ liquid-phase approach, a thin solid electrolyte (Li7 P3 S11 ) is coated on the surface of Te-doped sulfurized polyacrylonitrile. ● The combination of Te-doping and surface coating leads to enhanced reactivity and cycling stability in the all-solid-state battery.